Social investment and institutional change - Ciarini, Andrea (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book focuses on the main institutional changes affecting the Social Investment approach, as the framework for the European social agenda. The contributions gathered address these issues from different angles, placing two fundamental issues at the centre of the analysis. The first concerns the promotion of the strategic actions of European institutions and the national governments aimed at making social investment a recovery priority in the Eurozone. The second aims to make the social investment approach compatible not only with a high road to growth, as it is in the Stock-Flow-Buffer scheme, but also with the right to balance market and non-market activities as a universal right linked to a different combination of working and living time. It will be of interest to all scholars and students of social policy and European politics"--
OCLC-licensed vendor bibliographic record.
Keywords: Public welfare -- Europe; Welfare state -- Europe; Europe -- Social conditions; POLITICAL SCIENCE / Public Policy / Social Policy; POLITICAL SCIENCE / Public Policy / Social Security; POLITICAL SCIENCE / Public Policy / Social Services & Welfare